The Black Witch Chronicles: The Demon Tide - Book 4 - Forest, Laurie (Toronto, Ontario : Inkyard Press, 2022)
"Nothing can stop the demon tide...Newly exposed as the Black Witch of Prophecy, Elloren Gardner Grey is on the run, not knowing if she'll find friends or foes. With her fastmate, Lukas Grey, either dead or in the hands of High Mage Marcus Vogel, Elloren knows the only chance of turning the tide of the coming war is to seek allies who will listen long enough not to kill her on sight. In the Eastern Realm, Water Fae Tierney Calix and Elloren's brother Trystan have joined the Wyvernguard to prepare for Vogel's attack. But Trystan is fighting on two fronts, as the most despised and least trusted member of the guard. And Tierney's bond with Erthia's most powerful river has exposed a danger even more terrifying than the looming war. The Black Witch is back, and the Prophecy is at hand. It's time to fight. But Vogel has one more earth-shattering revelation for them all."--
Keywords: Witches -- Juvenile fiction; Magic -- Juvenile fiction; Prophecies -- Juvenile fiction; Imaginary wars and battles -- Juvenile fiction; Imaginary places -- Juvenile fiction; Fairies -- Juvenile fiction; Witches -- Fiction; Magic -- Fiction; Prophecies -- Fiction; Imaginary wars and battles -- Fiction; Imaginary places -- Fiction; Fairies -- Fiction; Fantasy; Fantasy fiction; Paranormal fiction